2020
DOI: 10.1111/jar.12778
|View full text |Cite
|
Sign up to set email alerts
|

“Look, all our hard work is paying off”: A qualitative evaluation of a system‐wide, workforce development model to promote positive behavioural support

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…in relation to the areas outlined in Table 1. These areas have been found in previous research to be important in the context of PBS approaches, such as developing and implementing PBS plans, staff confidence in managing behaviours that challenge and applying knowledge in practice (e.g., MacDonald et al, 2018;McKenzie, Martin, et al, 2020). Ratings were from 1 = very negative to 5 = very positive.…”
Section: The Impact Of Covid-19 On Pbsrelated Elementsmentioning
confidence: 89%
See 2 more Smart Citations
“…in relation to the areas outlined in Table 1. These areas have been found in previous research to be important in the context of PBS approaches, such as developing and implementing PBS plans, staff confidence in managing behaviours that challenge and applying knowledge in practice (e.g., MacDonald et al, 2018;McKenzie, Martin, et al, 2020). Ratings were from 1 = very negative to 5 = very positive.…”
Section: The Impact Of Covid-19 On Pbsrelated Elementsmentioning
confidence: 89%
“…The areas that were included have been found by researchers to be important in the context of PBS approaches, such as applying PBS knowledge in practice, developing PBS plans, implementing them in practice, and managing any behaviours that do occur with confidence (e.g. MacDonald et al, 2018; McKenzie, Martin, et al, 2020). As PBS aims to remove the need for the person to display behaviours that challenge, by providing functional alternatives, meaningful activities and improved quality of life (PBS Coalition UK, 2015), the impact on these areas was also measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was designed to address areas that are key components of PBS (e.g. Gore et al, 2013) and which had been explored in the wider evaluation study (McKenzie, Martin, et al, 2020). It included questions about the impact of Covid-19 on the quality of life, activities, behaviours that challenge and relationships of the people with an intellectual disability who were being supported by the participants.…”
Section: Methodsmentioning
confidence: 99%
“…An initial qualitative evaluation of the impact of the wider PBS approach, based on feedback from a range of stakeholders (McKenzie, Martin, et al, 2020) found that it was seen as having resulted in many benefits for people with an intellectual disability, individual staff, teams and organisations. The reported benefits included improvements in staff practice and knowledge; the adoption of better staff recruitment, supervision and performance management approaches; a reduction in staff turn‐over and sickness and improved quality of life of the people being supported by the organisations.…”
Section: Introductionmentioning
confidence: 99%